Efficacy of Botanicals against Helicoverpa armigera (Hubner) in Tomato (The Agriculturists, 2014)
Four botanicals viz., mahogany oil, mahogany seed extract, tobacco leaf extract, neem seed kernel extract along with one synthetic chemical, cypermethrin were tested for their efficacies against H. armigera. The lowest fruit infestation, both by number and weight, was observed in neem seed kernel extract (27.15%, 22.29%) treated plot which was statistically similar to tobacco leaf extract (27.71%, 23.31%) treated plot and cypermethrin (28.87%, 25.44%) treated fruits. While no significant difference was found among mahogany oil, mahogany seed extract and control treatments. Percent infestation reduction over control was the highest in neem seed kernel extract (30.08%) followed by tobacco leaf extract (28.68%). The highest yield (18.14 t/ha) and the highest MBCR (2.99) were also obtained from neem seed kernel extract treated fruits. DOI: http://dx.doi.org/10.3329/agric.v12i1.19868 The Agriculturists 2014; 12(1) 131-139